Investigation into a new method for monitoring snow temperature on cross-country ski tracks - Wagner, W. (Sports Technology, 2011)
Accurate predictions of snow surface temperature on cross-country race courses are crucial for optimal race ski preparation. This study investigates an easy and inexpensive method to monitor snow temperature at strategic locations on a racing track (e.g., southerly aspects, shaded areas and the stadium). Small self-contained temperature sensor dataloggers collect the average subsurface temperature between 1 and 2 cm, often where a skating ski rides. Temperature, temperature changes and trends are monitored the day, or days, prior to competition and examined to aid in ski preparation for upcoming events. Solar absorption of the sensors was the primary challenge and techniques to mitigate this issue were tested and are discussed. Results from a field study are presented, which give insight into the benefits and limitations for the usefulness of iButton temperature data for ski teams.